2018
DOI: 10.1111/fcp.12399
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine‐induced cytotoxicity and protection by heparin in mouse brain bEND.3 endothelial cells

Abstract: A pathological feature in atherosclerosis is the dysfunction and death of vascular endothelial cells (EC). Oxidized low-density lipoprotein (LDL), known to accumulate in the atherosclerotic arterial walls, impairs endothelium-dependent relaxation and causes EC apoptosis. A major bioactive ingredient of the oxidized LDL is lysophosphatidylcholine (LPC), which at higher concentrations causes apoptosis and necrosis in various EC. There is hitherto no report on LPC-induced cytotoxicity in brain EC. In this work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…You are encouraged to use the Version of Record that, when published, will replace this version. The most up-to-date-version is available at https://doi.org/10.1042/CS20210468 LPC-induced ROS generation seems to be endothelial cell typedependent since Tsai et al failed to observe this effect in cerebral bEND.3 endothelial cells [36]. Here, we found that LPC (10 -5 M) induces ROS production in a time-dependent manner in aortic endothelial cells (HAEC).…”
Section: Lpc Stimulates Calcium Influxmentioning
confidence: 59%
See 2 more Smart Citations
“…You are encouraged to use the Version of Record that, when published, will replace this version. The most up-to-date-version is available at https://doi.org/10.1042/CS20210468 LPC-induced ROS generation seems to be endothelial cell typedependent since Tsai et al failed to observe this effect in cerebral bEND.3 endothelial cells [36]. Here, we found that LPC (10 -5 M) induces ROS production in a time-dependent manner in aortic endothelial cells (HAEC).…”
Section: Lpc Stimulates Calcium Influxmentioning
confidence: 59%
“…Moreover, EGTA, an extracellular Ca +2 chelator, and Bapta-AM, an intracellular Ca +2 chelator, abrogated ROS generation induced by LPC stimulation at 15 min (figure 5C). LPC is an abundant component of oxidized low-density lipoprotein (oxLDL) [33][34][35][36], and blood LPC concentration is increased in unhealthy subjects [6,18,19], with values around 200 μmol Pi/L (micromoles of inorganic phosphate (Pi) per liter of plasma) in diabetic patients [18]. LPC activates apoptotic signaling [35][36][37], induces vascular dysfunction [33], promotes inflammatory cell infiltration of vascular walls [38], and induces innate immune trans-differentiation of endothelial cells [12].…”
Section: Lpc Stimulates Calcium Influxmentioning
confidence: 99%
See 1 more Smart Citation
“…In eukaryotic cells, PC is produced from phosphatidylethanolamine (PE) ( 45 ), in which LPC is an intermediate product of PC. LPC can react with acylCoA transferase in liver microparticles to produce PC ( 46 ). Besides, PC/LPC ratio in serum reflects inflammatory or infectious diseases of the liver.…”
Section: Resultsmentioning
confidence: 99%
“…LPC is an intermediate product of PC, which is hydrolyzed by PC under the action of PLA2 or Lecithin-cholesterol acyltransferase (LCAT). LPC can react with acylCoA transferase in liver microparticles to produce PC [47].…”
Section: Differential Metabolites Between Pcos-ms Group and Hc Groupmentioning
confidence: 99%